Hästars liggbeteende i aktiv grupphästhållning : komparativ studie mellan ligghallar med olika stora liggytor - Sjökvist, Matilda (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2019)
In the wild, horses live in smaller groups together in a herd. They spend most of the day feeding. One of many reasons why people choose to house their horses in different group-housing systems is because it is good for the horse’s welfare. An Active Stable® system helps horse-owners enrich the horses' environment with feeding at different locations several times a day, thus increasing the horse to be more active in the paddock for a long-term perspective.